Spatial proteomics reveals phenotypic and functional differences in T cell and macrophage subsets during villitis of unknown etiology - Petra K. Lothert; Bohdana Fedyshyn; Sylvie Girard; Rana Chakraborty; Andrew P. Norgan; Elizabeth Ann L. Enninga (Scientific Reports, 2024)
Abstract Villitis of unknown etiology (VUE) is a prevalent inflammatory pathology of the placenta characterized by infiltration of maternal T cells and accumulation of fetal macrophages into chorionic villi. VUE is associated with a variety of adverse clinical outcomes, including fetal growth restriction and fetal demise. Evaluation of the phenotypic and functional differences between two immune cell types associated with this pathology, namely T cells and macrophages, was completed to gain a deeper understanding of the immuno-pathogenesis of VUE. GeoMx Digital Spatial Profiling was performed on placental tissue from 4 high grade VUE cases and 4 controls with no underlying pathology. Placental tissues were fluorescently labeled with CD3 and CD68 antibodies and oligo-conjugated antibodies against 48 protein targets. Overall, T cells in VUE exhibited upregulated markers of activation, memory, and antigen experience compared to controls and were altered based on placental location (villi vs. decidua). Additionally, villous macrophages in VUE upregulated costimulatory and major histocompatibility complex class I and II molecules compared to controls and macrophage subtypes in the decidua. Data herein provides new mechanistic insights into T cell and macrophage biology in VUE which contribute to this abnormal immune response to pregnancy.